A internet dos leigos: catolicismo midiático e práticas de consumo como experiência vivida - Rosa, Ana Cássia Pandolfo Flores da (2018)
The research presents, as a theme, the action of the Catholic layman on the internet in the context of the mediatization of religion. The problematization constructs itself in the consideration of the insertion of the layman in the dynamics of the production and consumption of religious content on the internet and its impact on the religious experience of the subject. Thus, the problem question that guides the research is: how are the dynamics of production and consumption of religious content on the internet experienced by lay Catholics? To this end, the analysis arises from the blog The Catechist, a project created and maintained by lay people to deal with doctrinal issues and to approach current issues from a Catholic perspective. The study constructs itself as an analysis of ethnographic inspiration that is based on the methodological assumptions of the ethnography of the internet by Hine (2015) and that relied on the participation of eight privileged informants, namely the couple of bloggers responsible for The Catechist and six of its readers. The fieldwork was carried out through the observation of online participants on the blog and on the Catechist’s Facebook page, e-mail exchanges, conversations via chat applications, telephone interviews and two face-to-face visits with the bloggers. The interaction with the bloggers extended tor almost four years, from May 2014 to January 2018 and the contact with the readers was carried out from September 2017 to February 2018. The results point to the link between online and offline contexts, confirming the alignment of The Catechist's project with the idea of mediatic Catholicism (CARRANZA, 2011) that is characterized by a project of Catholic reinstitutionalization carried out by the media, which is characterized by a project of Catholic reinstitutionalization made effective by the media, moral and doctrinal conservatism and by the opposition to movements and ideas considered marxist / socialist / communist. The action of the bloggers, despite the freedom of initiative, to be firm in the idea of fidelity to the positions of the Church is taken as an unofficial protagonism. The constant need to renew their adherence to the institution is understood as a "tactical fidelity". The internet idea of the laity suggests that the catholic experience of the internet can be characterized by the experience of reaffirmation of the catholicity of the layman. According to the experience of internet readers, the reaffirmation of the Church's adherence is based on disputes of authority, morality and activism carried out through the dynamics of production and the consumption of religious content.